Smart Waste Management in Indonesia: A Review of AI and IoT Application, Challenges, and Future Directions for Sustainable Solutions - Nursetiawati; Fuqaha, Sameh (Graduate School, Universitas Brawijaya, 2024)
Waste management remains a significant challenge for Indonesia, as population growth and economic expansion continue to increase waste generation and strain existing disposal methods. Traditional approaches, such as open dumping, contribute to environmental degradation and inefficiencies in handling waste. However, the emergence of Artificial Intelligence (AI) and Internet of Things (IoT) technologies offers new opportunities to enhance waste management systems. This research explores the potential of AI and IoT in improving waste collection, sorting, recycling, and monitoring in Indonesia. By evaluating successful global implementations, it provides a framework for adapting these technologies to Indonesia’s unique challenges, with a focus on efficiency and sustainability. Key challenges, such as Accessibility and Reliability of Data , privacy concerns, infrastructure needs, and ethical considerations, are also addressed. In conclusion, while AI will offers great potential to improve waste management practices in Indonesia, it is crucial to address challenges such as data quality, privacy concerns, Financial and Infrastructure Requirements and Moral and Ethical Implications involved. With dedicated efforts and continuous research, AI's transformative capabilities can be fully utilized to promote sustainable and efficient waste management solutions in the country